Market-oriented AI algorithmic stock prediction and analysis - Deng, Yibo (Nanyang Technological University, 2024)
The aim of this report is to explore and evaluate the application of different machine learning algorithms in stock prediction. Machine learning, as a financial research method widely recognized by scholars nowadays, has a great advantage in the field of stock prediction due to its powerful self-learning and feature extraction capabilities. With the rapid development of information technology and the increasing attention of investors to the stock market, the accuracy and reliability of stock prediction becomes particularly important. In this study, various algorithms such as SVR, LSTM, MLP are selected to analyze and evaluate their performance in stock prediction by comparing the results.